The Use of Box Culvert Precast as a Main Bridge Structure in Arterial Highway Road: An Analysis Study - J Propika; L Lestari; J Muti (IPTEK Journal of Proceedings Series, 2018)
A bridge is a construction that connect two parts of the road cuts off by both natural and artificial obstacles. Meanwhile, a box culvert is a rectangular precast concrete structure that has a basic function as underground construction in the form of culverts, drains, and other supporting constructions. Those function of the box culvert is now developing as the main structure in the construction of bridges and highways. Thus, a research and evaluation should be done. The performance of the existing box culvert structures is in accordance with SNI 1725: 2016 regulations. The research methodology is done by manual calculation to get the load and reinforcement needs, while for static analysis by modelling the structure in SAP 2000 V.14.2.5 program. The material used is the existing material for top-bottom box culvert type (4000 x 4000 x 1500) fc '= 30 MPa and fy = 400 MPa. The results shows the reinforcement does not meet the minimum requirements of strong box structure reinforcement against bridge construction loads. The reinforcement ratio in plate slab area are almost close to the maximum ratio of reinforcement requirements. Whereas in the box culvert wall area, there is an over-reinforcement so the dimensions must be increased.